1997
DOI: 10.1021/la962095h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oriented Zeolite Membranes at the Interface between Two Fluid Phases

Abstract: A method was developed for the synthesis of free-standing silicalite-1 membranes. Intergrown polycrystalline films were synthesized at the interface between a colloid-free aqueous phase and an organic phase or air. These films were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). It was found that the crystallites of the films formed at the air-water interface were oriented with their (010) axis orthogonal to the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Schu ¨th, Fowler and others grew zeolite structures or silica spheres at such interfaces, but failed to generate structures with defined pore sizes and size distribution. [24][25][26][27][28] Pore size control in microparticle colloidal assemblies were reported by Dinsmore et al, using assembly of the particles at fluid interfaces, followed by sintering. The resulting interstices of the quasi-hexagonal array of particles gave pores in the range of several hundred nanometers.…”
Section: Nanoparticles As Building Blocksmentioning
confidence: 94%
“…Schu ¨th, Fowler and others grew zeolite structures or silica spheres at such interfaces, but failed to generate structures with defined pore sizes and size distribution. [24][25][26][27][28] Pore size control in microparticle colloidal assemblies were reported by Dinsmore et al, using assembly of the particles at fluid interfaces, followed by sintering. The resulting interstices of the quasi-hexagonal array of particles gave pores in the range of several hundred nanometers.…”
Section: Nanoparticles As Building Blocksmentioning
confidence: 94%
“…For a b-oriented ZSM-5 membrane, such issues still remain an open question. b-Oriented ZSM-5 membranes have been reported by Jansen et al, [27] Yan et al, [28] Tricoli et al [29] and Wang et al, [10,30,31] however no permeation data was reported for these membranes.…”
Section: Full Papermentioning
confidence: 96%
“…to the surface of the support. Tricoli et al 1997 developed self-standing silicalite-1 films by a hydrothermal method on Ž . an air᎐water interface, to which the 0k0 axis was orthogo-Ž .…”
mentioning
confidence: 99%